2014
DOI: 10.1182/blood.v124.21.120.120
|View full text |Cite
|
Sign up to set email alerts
|

First-in Man, Phase 1 Study of CSL362 (Anti-IL3Rα / Anti-CD123 Monoclonal Antibody) in Patients with CD123+ Acute Myeloid Leukemia (AML) in CR at High Risk for Early Relapse

Abstract: Background: Most patients with acute myeloid leukemia (AML) die from relapsed disease, including those who attain complete remission (CR). Post-remission treatment designed to kill chemoresistant leukemia stem cells (LSC) and eradicate minimal residual disease (MRD) could delay or prevent relapse. The Interleukin-3 Receptor alpha chain (IL3Rα/CD123) is overexpressed on LSC and AML blasts compared to normal hematopoietic cells. CSL362 is a fully humanized anti-CD123 monoclonal antibody, engineered for greater a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(27 citation statements)
references
References 0 publications
1
25
0
1
Order By: Relevance
“…A phase I trial in AML (clinical trial NCT01632852) using intravenously administered CSL362 in doses ranging from 0.3 to 12.0 mg/kg has recently been completed (43). In that study, there were no increased infections despite rapid (≤6 hours after dose) and complete pDC and basophil depletion at all doses for a fortnightly dosing frequency, which was sustained for ≥15 days for doses ≥3 mg/kg; however, a phase II trial will provide data regarding longer-term infection risk.…”
Section: Discussionmentioning
confidence: 99%
“…A phase I trial in AML (clinical trial NCT01632852) using intravenously administered CSL362 in doses ranging from 0.3 to 12.0 mg/kg has recently been completed (43). In that study, there were no increased infections despite rapid (≤6 hours after dose) and complete pDC and basophil depletion at all doses for a fortnightly dosing frequency, which was sustained for ≥15 days for doses ≥3 mg/kg; however, a phase II trial will provide data regarding longer-term infection risk.…”
Section: Discussionmentioning
confidence: 99%
“…Strategies that use the immunological properties of antibodies to enhance antibody-dependent cell-mediated toxicity are also being pursued. Bispecific CD33 41 and CD123 42 antibodies linked to CD3 are being developed, as is a CD123 antibody linked to CD16, 43 meant to deliver cells expressing these targets into the vicinity of T cells or natural killer cells, respectively. Another novel approach involves targeting the CD47 antigen, preventing it from interacting with its cognate macrophage receptor SIRP1-a; preclinical studies have shown this disruption can lead to the activation of innate immunity and macrophage-mediated destruction of LSCs.…”
Section: Aberrant Immunophenotypesmentioning
confidence: 99%
“…CSL362 is a humanized second-generation anti-CD123 antibody with favorable preclinical data [ 67 ] that was found to be safe and well tolerated as maintenance therapy in a phase I study of AML patients with CR + CRp and high risk of relapse (NCT01632852) [ 68 ]. A phase 2 study of CSL362 is planned.…”
Section: Immunotherapymentioning
confidence: 99%